Reactivity of larger intracranial arteries using 7 T MRI in young adults. Issue 7 (July 2019) - Al-Khazraji, Baraa K; Shoemaker, Leena N; Gati, Joseph S; Szekeres, Trevor; Shoemaker, J Kevin
The larger intracranial conduit vessels contribute to the total cerebral vascular resistance, and understanding their vasoreactivity to physiological stimuli is required when attempting to understand regional brain perfusion. Reactivity of the larger cerebral conduit arteries remains understudied due to a need for improved imaging methods to simultaneously assess these vessels in a single stimulus. We characterized reactivity of basal intracranial conduit arteries (basilar, right and left posterior, middle and anterior cerebral arteries) and the right and left internal carotid arteries, to manipulations in end-tidal CO2 (PetCO2 ). Cross-sectional area changes (%CSA) were evaluated from high-resolution (0.5 mm isotropic) images collected at 7 T using a T1-weighted 3D SPACE pulse sequence, providing high contrast between vessel lumen and surrounding tissue. Cerebrovascular reactivity was calculated as %CSA/ΔPetCO2 in eight healthy individuals (18–23 years) during normocapnia (41 ± 4 mmHg), hypercapnia (48 ± 4 mmHg; breathing 5% CO2, balance oxygen), and hypocapnia (31 ± 8 mmHg; via hyperventilation). Reactivity to hypercapnia ranged from 0.8%/mmHg in the right internal carotid artery to 2.7%/mmHg in the left anterior cerebral artery. During hypocapnia, vasoconstriction ranged from 0.9%/mmHg in the basilar artery to 2.6%/mmHg in the right posterior cerebral artery. Heterogeneous cerebrovascular reactivity to hypercapnia and hypocapnia was characterized across basal intracranial conduit and internal carotid arteries.